Transient hypofibrinogenemia due to allopurinol - Yin ZQ; Xu JL; Li YQ; Xia JP; Luo D (Dove Medical Press, 2014)
ZhiQiang Yin,1,* JiaLi Xu,2,* YongQiang Li,3,* JiPing Xia,1 Dan Luo1 1Department of Dermatology, 2Department of Oncology, 3Department of Rehabilitation Medicine, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, People's Republic of China *These authors contributed equally to this work Abstract: This study reports a case of an 80-year-old male who suffered from drug eruption due to oral allopurinol for the treatment of gout. This patient complained of widespread erythema and maculopapule with itch, and small quantities of purplish-red rash with diffused distribution on four limbs were noted. After he was hospitalized, the area with purpuric rash increased in size, and hypofibrinogenemia was found. After treatment with intravenous infusion of fibrinogen and cryoprecipitate, and continued treatment with high-dose methylprednisolone, the skin rash gradually went away. This is the first report of purpura and hypofibrinogenemia induced by allopurinol and the pathophysiology underlying this reaction remained unknown. Keywords: purpura, fibrinogen, drug eruption, gout